A critical analysis of species selection and high vs. low-input silviculture on establishment success and early productivity of model short-rotation wood-energy cropping systems. (March 2017) - Fischer, M.; Kelley, A.M.; Ward, E.J.; Boone, J.D.; Ashley, E.M.; Domec, J.-C.; Williamson, J.C.; King, J.S.
Abstract: Most research on bioenergy short rotation woody crops (SRWC) has been dedicated to the genera Populus and Salix . These species generally require relatively high-input culture, including intensive weed competition control, which increases costs and environmental externalities. Widespread native early successional species, characterized by high productivity and good coppicing ability, may be better adapted to local environmental stresses and therefore could offer alternative low-input bioenergy production systems. To test this concept, we established a three-year experiment comparing a widely-used hybrid poplar ( Populus nigra × P. maximowiczii, clone 'NM6') to two native species, American sycamore ( Platanus occidentalis L.) and tuliptree ( Liriodendron tulipifera L.) grown under contrasting weed and pest control at a coastal plain site in eastern North Carolina, USA. Mean cumulative aboveground wood production was significantly greater in sycamore, with yields of 46.6 Mg ha −1 under high-inputs and 32.7 Mg ha −1 under low-input culture, which rivaled the high-input NM6 yield of 32.9 Mg ha −1 . NM6 under low-input management provided noncompetitive yield of 6.2 Mg ha −1 . Sycamore also showed superiority in survival, biomass increment, weed resistance, treatment convergence, and within-stand uniformity. All are important characteristics for a bioenergy feedstock crop species, leading to reliable establishment and efficient biomass production. Poor performance in all traits was found for tuliptree, with a maximum yield of 1.2 Mg ha −1, suggesting this native species is a poor choice for SRWC. We conclude that careful species selection beyond the conventionally used genera may enhance reliability and decrease negative environmental impacts of the bioenergy biomass production sector. Highlights: High-input management is needed for establishment of traditional bioenergy systems. Low vs. high-input bioenergy hardwood systems were evaluated in North Carolina, USA. Overall growth performance ranked as follows: Sycamore > NM6 ≫ Tuliptree. Low-input sycamore productivity matched widely reported high-input poplar cultures. Species selection for robust establishment may confer further bioenergy benefits.